2017
DOI: 10.3389/fmats.2017.00035
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of Food Packaging-Related Properties of Whey Protein Isolate-Based Nanocomposite Films and Coatings by Addition of Montmorillonite Nanoplatelets

Abstract: In this study, the effects of the addition of montmorillonite (MMT) nanoplatelets on whey protein isolate (WPI)-based nanocomposite films and coatings were investigated. The main objective was the development of WPI-based MMT nanocomposites with enhanced barrier and mechanical properties. WPI-based nanocomposite cast films and coatings were prepared by dispersing 0% (reference sample), 3, 6, 9% (w/w protein) MMT, or, depending on the protein concentration, also 12 and 15% (w/w protein) MMT into native WPI-base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 66 publications
2
15
0
Order By: Relevance
“…The nanoclay particles act as physical barriers against the movement of water molecules, that is, WVP is decreased by the tortuous path created by the nanoclay particle for diffusion of water molecules. 64,65 The results are well supported by the TEM analysis.…”
Section: Resultssupporting
confidence: 69%
“…The nanoclay particles act as physical barriers against the movement of water molecules, that is, WVP is decreased by the tortuous path created by the nanoclay particle for diffusion of water molecules. 64,65 The results are well supported by the TEM analysis.…”
Section: Resultssupporting
confidence: 69%
“…WPI was obtained from Agropur Ingredients (Saint-Hubert, Laval, QC, Canada; previously Davisco Food International Inc.). Aqueous nanoclay dispersions were provided by ITENE, Valencia, Spain, as described in our previously published results [34]. The plasticising agent, as selected in a prior published study that focused on formulation optimization [34], was purchased from Panreac S.A., Barcelona, Spain to be used as a plasticiser for the WPI-based film-forming formulations.…”
Section: Methodsmentioning
confidence: 99%
“…Aqueous nanoclay dispersions were provided by ITENE, Valencia, Spain, as described in our previously published results [34]. The plasticising agent, as selected in a prior published study that focused on formulation optimization [34], was purchased from Panreac S.A., Barcelona, Spain to be used as a plasticiser for the WPI-based film-forming formulations. As a substrate for the coatings, chemically pre-treated poly (ethylene terephthalate) (PET) with thicknesses of 23 and 100 µm, respectively (PLASTIKA-ANDREJ MESOJEDEC S.P., Polje, Slovenia), were respectively used for the application of coating formulations using a pilot-scale and a semi-industrial-scale processing environment.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Likewise, the use of edible-coated nanosystems has also been considered as a novel approach for food preservation. Findings have lately suggested that novel WPI-based nanocomposites can be part of multilayer flexible packaging films, thus holding great potential to even replace well-established fossil-based packaging materials to support certain mechanical properties during storage [151,153,155,163]. Alternative biomaterials, have also been recently proposed for potential uses in foodstuff applications, via the production of nanocomposites from WPCs activated with lycopene and montmorillonite nanoparticles [164,168].…”
Section: Whey Proteins: Research Insights and Trendsmentioning
confidence: 99%